ORIGINAL ARTICLEEchocardiographic assessment of left ventricle function in children with scleromyositis - Borowiec-Kocańda, Anna; Woźniak, Jacek; Firek, Bohdan; Kwiatkowska, Małgorzata; Dąbrowski, Rafał; Musiej-Nowakowska, Elżbieta; Kowalik, Ilona; Romicka, Anna Maria; Szwed, Hanna (Reumatologia/Rheumatology, 2006)
Introduction: Possibility of heart pathology in children with scleromyositis is still an open clinical problem. The aim of the study: Echocardiographic assessment of possible changes in heart muscle in this group of patients. Material and methods: We studied 18 children with scleromyositis (11 girls and 7 boys), age: 15.8±2.6 years with no clinical signs or symptoms of heart disease. Control group comprised 20 healthy children, age: 13.8±2.7 years. M-mode, 2-D and Doppler echo was performed in all subjects and global index of LV performance ( Tei index ) was calculated as a proportion of the sum of isovolumetric contraction time (ICT) and isovolumetric relaxation time (IVRT) to ejection time (ET). Results: LA diameter was significantly lower in children with scleromyositis than in control group: 2.7±0.3 vs 3.1±0.3; p<0.01. Value of PWd in scleromyositis group was 0.6±0.15 and was significantly lower in comparison with control group: 0.8±0.15; p<0.005. There was no significant difference in value of LVdD, LVsD, IVSd, SF i EF in both groups. Also E/A, ICT, IVRT i ET values were similar in both groups. Tei index in scleromyositis group and in control group was: 0.46±0.08 and 0.44±0.06 respectively, p=NS. Conclusion: Based on analysis of echocardiographic parameters there are no changes in heart muscle in children with scleromyositis which suggests that cardiac involvement is not an early sign of the disease.